Urbach-Wiethe disease (lipoid proteinosis) - Ulku Kucuk; Isin G Erdogan; Umit Bayol; Nazife Hacioglu; Ibrahim Cukurova; Cengiz Bicakci (Wolters Kluwer Medknow Publications, 2012)
Lipoid proteinosis is a rare autosomal recessive disorder of variable severity that may involve the skin, mucous membranes of the upper respiratory tract and internal organs that may display different clinical manifestations based on the site of involvement. A 34-year-old male patient was admitted to our hospital with a complaint of hoarseness present since childhood but had worsened in recent years. A dermatological examination revealed light brown papillomatous skin lesions on the dorsum of both hands and elbows present for a long duration. Endoscopic examination of the larynx revealed widespread mucosal thickening and irregularity. Microscopic examination revealed acid Schiff (PAS) positive, Congo red negative eosinophilic hyaline material deposits in the dermis and submucosal regions. The final diagnosis was lipoid proteinosis with skin and larynx involvement. This typical case has been reported to draw attention to the fact that lipoid proteinosis should be included in the differential diagnosis of patients presenting with hoarseness in childhood.